The effects of activated biochar addition on remediation efficiency of co-composting with contaminated wetland soil - Ye, Shujing; Zeng, Guangming; Wu, Haipeng; Liang, Jie; Zhang, Chang; Dai, Juan; Xiong, Weiping; Song, Biao; Wu, Shaohua; Yu, Jiangfang (Resources, conservation and recycling, 2019)
[Display omitted] •Using agricultural biomass to achieve high remediation efficiency and waste recycling.•Activated biochar with modified pore structure showed positive effects on composting process.•Higher remediation efficiency of polluted soil was observed in activated biochar addition.•Changes in microbial number and ratio of bacterial/ fungi were accounted for pollutant removal. Unreasonable disposal of organic wastes has caused great problems, including occupying land, affecting organoleptic feeling and causing environmental re-contamination. By incorporation of biochar as raw material into co-composting with agricultural organic matter, it not only can the wastes recycling be realized, but also can the remediation efficiency of multi-element contaminated soil be improved to reach land reclamation. Activated biochar was added for investigating the influences on physico-chemical properties of soil during composting. The concentrations of available metals and arsenic in soil were detected on great reduction in the treatment of biochar-blended composting. Based on the stronger adsorption and microbial activity induced by biochar, the initial content of available PAHs in wetland soil decreased to remain about 3.03% and 5.47% below the control (9.47%) in co-composting added with activated and fresh biochar, respectively. It was related to the observation with improved microbial number as well as optimized fungi/bacteria gene copy number ratio by activated biochar addition, which is conducive to vegetation replanting of contaminated land. The feasibility of applying biochar into co-composting with contaminated soil was confirmed by not only the high remediation efficiency but also the sustainable recycling of agricultural waste.